2016
DOI: 10.1007/s10661-016-5405-1
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder prevalence and associations with air concentrations of lead, mercury, and arsenic

Abstract: Lead, mercury, and arsenic are neurotoxicants with known effects on neurodevelopment. Autism spectrum disorder (ASD) is a neurodevelopmental disorder apparent by early childhood. Using data on 4486 children with ASD residing in 2489 census tracts in five sites of the Centers for Disease Control and Prevention's Autism and Developmental Disabilities Monitoring (ADDM) Network, we used multi-level negative binomial models to investigate if ambient lead, mercury, and arsenic concentrations, as measured by the US E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 54 publications
(95 reference statements)
1
41
0
1
Order By: Relevance
“…In contrast, ADDM typically surveys 4 urban counties in New Jersey, but samples Alabama broadly across 32 counties in the northern half of the state, comprising a mix of urban and rural areas. ASD prevalence in general tends to be higher in urban than rural areas, for reasons that are not clear but may involve enhanced exposure to beneficial environmental microbes in rural areas and/or higher levels of toxins in urban areas (Becker 2010; Dickerson et al 2016). As a result, the different sampling strategies across the two states will tend to exaggerate the difference in ASD prevalence between New Jersey and Alabama.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ADDM typically surveys 4 urban counties in New Jersey, but samples Alabama broadly across 32 counties in the northern half of the state, comprising a mix of urban and rural areas. ASD prevalence in general tends to be higher in urban than rural areas, for reasons that are not clear but may involve enhanced exposure to beneficial environmental microbes in rural areas and/or higher levels of toxins in urban areas (Becker 2010; Dickerson et al 2016). As a result, the different sampling strategies across the two states will tend to exaggerate the difference in ASD prevalence between New Jersey and Alabama.…”
Section: Discussionmentioning
confidence: 99%
“…Yasuda et al [16,17] mg•kg − 1 ). Similar Pb and As content were found in the hair of ASD children from different parts of the world, Saudi Arabia [11,12,18,43], Kuwait [25], Oman [19], India [20], Egypt [21,22], Italy [26], and the USA [5,29,44].…”
Section: Discussionmentioning
confidence: 63%
“…In children whose mothers were exposed to As compounds, the following symptoms are observed: difficulty with learning, memory, concentration, cognitive and behavioral disorders. Children exposed to this element may also present the symptoms of retarded development or inhibited physical and mental development [1,5,6,13,23,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, studies have demonstrated that increased levels of lead (Pb), mercury(Hg), and arsenic(As) in the air are associated with an increased prevalence of ASD [1]. In addition, data from the center for disease control and prevention of the USA have demonstrated the associations of environmental levels of Pb, Hg, and As with ASD [2].…”
Section: Introductionmentioning
confidence: 99%